Extending LEAN Mapping to Subsurface Scattering - Tiago André da Silva Vila Verde (2015)
The goal of this thesis is to extend LEAN Mapping to incorporate the Subsurface Scattering effect which exists on translucent materials, such as marble or skin, while producing a model that is sufficiently simple in order to be easily incorporated into current art assets and pipelines. For the success of this project it is therefore important to know what is the current state of shading models in terms of the subsurface scattering effect, as well as what is LEAN mapping and how it can be incorporated into popular models. This document provides an overview of the most important concepts for such an understanding. Typically, a subsurface scattering effect is obtained by blurring the diffuse texture, however, previous works have found that by having each individual RGB normal pointing in different directions, it is possible to achieve a realistic scattering effect. This means that it could, potentially, be possible to apply those blurs to normal maps and have similar results. By applying it to the LEAN maps, we can further refine the process to include more detailed specular highlights. This can be done by having a deferred rendering approach and applying the blur to the G-Buffer. However, object curvature can be important depending on how curved the object is and how deep the light penetrates. By projecting onto a common plane, it is possible to capture that information and the blur can then be applied. Result comparison with previous works shows the elimination of some artifacts. Nevertheless, in frame rate terms, there is a significant decrease in performance, attributed to the number of textures being blurred. On average, rendering a frame takes about four times longer. In short, the work presented in this document is valid and shows some promise in subsurface scattering contexts, however, it can certainly be improved in the future.